A Review of Breast Cancer Classification and Detection Techniques - Mohamed, Sarah Khaled; Sakr, Nehal A.; Hikal, Noha A. (SOTVI, 2021)
Cancer is a very serious disease. Deadly and very hard if you lived with. Cancer is caused when abnormal changes happens on cells that are out of control.Cancer cells often form a lump or mass called a tumor and are named after the part of the body in which they originated. When Happens at breast organ it is called Breas Cancer. Deadly as any other type of cancer. Also as any other type, it has a life cycle consist of stages. usually does not produce any pain in the early stages in which it is easy to treat on. Cancer main problem is when to find out that the patient had cancer cell inside his body. Early stages always it better timing to start treating the cancer tumors. All old reaserchers and doctors always tried to improve the medical processe in which we try to find cancer cells also the other medical checkups to help us detect or even predict that this person had or will have a cancer disease in the future. CAD systems and Medical Screening was the main ways to think about. Medical Images processing technologies and finding best features of cells was the right way and using CNN, Deep CNN, Convoltion Matricese, SVM Technique and many of Machine Learning algorithms used before, the main challenge was to make it easy and also more accurate to complete these tests. Many improvements made at this track of work. The results always was More and more of accuracy improvements and time reduction and resources usage improvements too.